Spatiotemporal distribution of PTEN before directed cell migration in monolayers - Lu, Quanzhi; Sasaki, Saori; Sera, Toshihiro; Kudo, Susumu (In vitro cellular & developmental biology. Animal, 2024)
The intracellular distribution of phosphatase and tensin homolog (PTEN) is closely related to directed cell migration. In single cells, PTEN accumulates at the rear of the cell before and during directed migration; however, the spatiotemporal distribution of PTEN in confluent cell monolayers, particularly before directed migration, remains unclear. In this study, we wounded a cell in confluent fetal rat skin keratinocytes (FRSKs) and examined the dynamics of PTEN in the cells adjacent to the wounded cell. In contrast to single-cell migration, we found that PTEN translocated to the nucleus before the beginning of directed migration. This nuclear translocation of PTEN did not occur in disconnected cells, and it was also suppressed by importin-β inhibitor and actin inhibitor. When the nuclear localization of PTEN was inhibited by an importin-β inhibitor, cell elongation in the direction of migration was also significantly inhibited. Our results indicate that PTEN translocation is induced by the disruption of cell-cell adhesion and requires the involvement of importin-β and actin cytoskeleton signaling. In addition, phosphatidylinositol 3,4,5-triphosphate (PIP3) may regulate PTEN distribution through its localized accumulation at the cell edge. Our findings suggest that the translocation of PTEN is crucial for directed cell migration and for responding to mechanical environmental changes in confluent cell monolayers.